Rumah Wan Aisyah, 1468 Jalan Sultanah Zainab, Kota Bharu, Kelantan - Sirajul Adli Shahidan; Haslina Kamaruddin; Nurul Aqmar Hassan; Awang Asnawi Jaafar; Azrul Rizad Othman; Lim, Hsiao Fui @ Juliana; Mohd. Zikri Rodzi (Skudai : Universiti Teknologi Malaysia, 1998)
Kajian Lukisan Terukur (Jabatan Senibina) - Universiti Teknologi Malaysia, 1998